Critical Thinking Dalam Al-Qur’an: Studi Tafsir Tematik dan Implementasinya di Era Digital - Qithrotun Nida Aulia; Sholahuddin Al Ayubi; Salim Rosyadi (Jurnal test, 2025)
The rapid development of information technology has led to the proliferation of information circulating in the digital era, both valid and invalid information. This phenomenon requires the ability of individuals to sort and evaluate the information sharply by applying critical thinking. This study aims to examine the verses of the Qur'an that are in line with the principles and theories of critical thinking and their implementation to problems in the digital era through a thematic interpretation approach. The research method used in this study is a literature study (library research) with a qualitative approach. The results of this study explain that the verses of the Qur'an and also interpretations that are in line with the concept of critical thinking are found in Q.S. Al-Hujurat: 6, Q.S. Al-Isra: 36, Q.S. Maryam: 42, Q.S. Az-Zumar: 18, Q.S. An-Nahl: 125, Q.S. Al-Baqarah: 170 and Q.S. An-Nisa: 135. The interpretation of these verses explains the importance of verifying information (tabayyun), healthy skepticism, rational thinking, being selective about information, being open-minded, and also being objective in thinking and acting.